Optimasi Desain Jembatan Gantung Dengan Menggunakan Material Komposit Serat Karbon Untuk Peningkatan Efisiensi Dan Daya Tahan - Deki Sipul Umbu Hina (CV. SINAR HOWUHOWU, 2025)
This study aims to optimize the design of suspension bridges by utilizing carbon fiber composite materials to enhance structural efficiency and long-term durability. Employing a quantitative methodology, this research compares two bridge design models—a conventional model (steel) and an innovative model (carbon fiber composite)—through numerical simulations based on the Finite Element Method (FEM). The analysis results indicate that the use of carbon fiber composites leads to a significant reduction in total structural weight (up to 45%), which substantially decreases the load on foundations and towers. Furthermore, the composite model demonstrates a more stable dynamic response, with a higher natural frequency that improves its resistance to wind and seismic resonance, a critical factor for long-span bridges. In terms of durability, carbon fiber composites excel due to their inherent corrosion resistance and fatigue resistance, potentially reducing lifetime maintenance costs. Although the initial material cost of composites is higher, a life-cycle cost analysis suggests that long-term savings from maintenance can offset this initial investment. The study concludes that carbon fiber composite material is a technically superior and viable alternative for modern suspension bridge design, offering a lighter, stronger, and more sustainable solution for future infrastructure.